THE AUTHORITY OF THE PUBLIC PROSECUTOR IN CARRYING OUT CONFISCATION OF EVIDENCE OF CORRUPTION CRIMINAL ACTS IN PROSECUTION STAGE - Ris Piere Handoko; Mhd Azhali Siregar; Muhammad Arif Sahlepi (PT. Radja Intercontinental Publishing, 2025)
The Criminal Procedure Code (KUHAP) expressly authorizes investigators to confiscate in order to maintain the security and integrity of these objects, but the confiscation must be based on the conditions and procedures determined by law and the confiscation is intended for the purpose of proof, especially as evidence in court. The research method used is a normative juridical research approach, namely an approach carried out by examining theoretical approaches, concepts, reviewing laws and regulations related to the implementation of the authority of the Public Prosecutor in confiscating evidence of corruption crimes at the Prosecution Stage. Based on research that the legal process of confiscating evidence of corruption by the Public Prosecutor at the Prosecution Stage, if during the trial legal facts are found related to the defendant's assets that have not been confiscated at the investigation stage, then the Public Prosecutor can submit a request for confiscation permission to the Panel of Judges then after being granted then the Panel of Judges issues a Determination of Confiscation Permit from the Panel of Judges, Furthermore, the Public Prosecutor in following up on the determination makes a Minutes of Implementation of the Judge's Determination and Minutes of Implementation of Confiscation which are then attached to the case file and stated in the indictment regarding evidence.